2015
DOI: 10.1093/pubmed/fdv086
|View full text |Cite
|
Sign up to set email alerts
|

Contributions of individual acculturation and neighborhood ethnic density to variations in Hispanic children's respiratory health in a US–Mexican border metropolis

Abstract: Results suggest that increasing individual-level acculturation is detrimental for US Hispanic children's respiratory health in this Hispanic majority setting, while high ethnic density neighborhoods are mildly risky and pose more significant threats when other individual-level factors are present.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…To date, 93% of the world's children live in areas where particulate matter levels are above WHO air‐quality guidelines 40 . Air pollution is a cause of exacerbation of lung diseases including asthma, elevated pregnancy risks including low birth weight and prematurity, as well as slower attainment of developmental milestones and reduced cognitive function 41,42 …”
Section: The Impact Of Climate Change On the Health Of Girlsmentioning
confidence: 99%
“…To date, 93% of the world's children live in areas where particulate matter levels are above WHO air‐quality guidelines 40 . Air pollution is a cause of exacerbation of lung diseases including asthma, elevated pregnancy risks including low birth weight and prematurity, as well as slower attainment of developmental milestones and reduced cognitive function 41,42 …”
Section: The Impact Of Climate Change On the Health Of Girlsmentioning
confidence: 99%
“…We previously demonstrated that acculturation (defined as generation in the United States) partially explains the association observed between high socioeconomic status and diagnosed asthma in Mexican American children living in the San Francisco Bay Area. 33 Grineski et al demonstrated that high acculturation, derived from an abbreviated version of the Cultural Life Style Inventory, was significantly associated with asthma in Hispanic youth from El Paso, Texas, 34 even after considering neighborhood factors 35 ; however, after accounting for undiagnosed asthma, this association no longer persisted. 36 Another study, after accounting for native genetic ancestry, also did not demonstrate an association between acculturation and asthma.…”
mentioning
confidence: 99%